ANALISI YURIDIS PENGATURAN JANGKA WAKTU NOTARIS DALAM MENERIMA DAN MENYIMPAN PROTOKOL NOTARIS DI INDONESIA - Diki Zukriadi; Padrisan Jamba; Zuhdi Arman (Jurnal Cahaya Keadilan, 2021)
Notary Public is a public official who is authorized to make credential deeds as a means of proof. Besides being given a notary protokol, it is also obliged to save the notary protokol, both its own and other notary protokols. Regulations related to depository of notary protokol in article 65 paragraph (5) of the UUJN only state that the time for submission was issued 25 (twenty-five) years or more sent by the Notary recipient of the Notary Protokol to the Regional Supervisory Council. This can lead to legal considerations of the notary who will accept the protokol responsible for the notary protokol which is of great concern, which causes rejection of other notaries who will accept the protokol. This study uses a normative method with steps of description, systematization, and explanation of the content of positive law related to using laws and regulations, accessing history and obtaining concepts. Based on the results of the assessment and analysis, the notary protokol is not regulated by the exploitation in UUJN so as to make an agreement on the law so that it can keep documents on the notary protokol while he is still working and also open the work agreement by getting permission from the Notary Association Regional Supervisory Board. Indonesia. While it was agreed that there was a refusal to accept the notary protokol, legal considerations would be given to the notary recipient of the protokol. Tackling these responsibilities can be incorporated into codes of ethics, the notary profession, and approved by the government regarding sanctions for reprimands and compensation from membership.